Optimalisasi Manajemen Sumber Daya Manusia Dosen Fakultas Tarbiyah Dan Ilmu Keguruan (FTIK) Universitas Islam Negeri (UIN) Sjech M. Djamil Djambek Bukittinggi - Syamsurizal, Syamsurizal; Ilmi, Darul (Journal of Islamic Education Leadership, 2023)
Otimalization of Human Resource Management for Lecturers at the Faculty of Tarbiyah and Teacher Training, Sjech M. Djamil State Islamic University, Bukittinggi. This study aims to explain the management of lecturer human resource management, analyze patterns of optimizing the performance of lecturer human resources, transform challenges in managing lecturer human resource management, and describe the constraints/obstacles in managing human resource management for lecturers of the Faculty of Tarbiyah and Teaching Science (FTIK) UIN Bukittinggi. This study uses a qualitative approach. Data collection techniques were carried out using interviews, observation, and documentation. The results showed that: 1) Lecturer HR management was carried out through several stages, namely the planning stage, the organizing stage, the actuating stage, and the controlling stage. 2) Patterns of Optimizing the Performance of Human Resources for Lecturers of the Faculty of Tarbiyah and Teaching Sciences (FTIK) Bukittinggi State Islamic University include: optimizing the pedagogical competency aspect, optimizing the personality competency aspect, optimizing the social competency aspect, and optimizing the professional competency aspect. 3) Challenges affecting lecturer HR in optimizing organizational performance at the Faculty of Tarbiyah and Teaching Science (FTIK) Bukittinggi State Islamic University. The research results have a positive impact, namely 1) Lecturers and Education Staff can evaluate organizational performance at the Faculty of Tarbiyah and Teacher Training (FTIK) Bukittinggi State Islamic University. 2) Forming solidarity between lecturers, educational staff, and leaders of the Faculty of Tarbiyah and Teaching Science (FTIK) Bukittinggi State Islamic University. 3) Optimizing the performance of lecturers' human resources in managing higher education institutions. The negative impacts are 1) There are still difficulties in optimizing facilities and the welfare of lecturers due to a lack of funding, and 2) it is still in the development stage where lecturers still need a lot of guidance and support. 3). some lecturers need time to adapt after the performance evaluation